Layer-wise control of selective laser melting by means of inline melt pool area measurements - Vasileska, Ema; Demir, Ali Gökhan; Colosimo, Bianca Maria; Previtali, Barbara (Laser Institute of America, 2020)
Industrial selective laser melting (SLM) systems commonly employ a fixed set of process parameters throughout the build of the same component. The process parameters are generally found by experimental studies carried out on simple geometries which achieve high density. A common issue is related to the fact that the single set of parameters can be inadequate for small sections and overhang regions where thermal accumulation can occur. An online adaptation of process parameters is required for avoiding such issues and defects that commonly arise, such as the swelling phenomenon. A real-time control strategy would be desirable. However, the real-time control requires fast acquisition and reaction in the order of microseconds. Another approach is to provide corrective actions in a layer-wise fashion by elaborating the monitoring data collected during the previous layer. Therefore, this work proposes a layer-wise control strategy based on coaxial melt pool monitoring. For this purpose, an open SLM platform is employed, fitted with a complementary metal-oxide semiconductor camera, to view the process emission in the near infrared region. Initially, the nominal level of the melt pool area is defined on a simple geometry. Then, the melt pool area is monitored on more complex shapes. The melt pool area measured on each scan vector of a given layer is used to compensate the energy density of the same scan vector at the next layer. The results show an effective reduction of swelling defects on small geometries with fine details.